Changing the cost of care for chronic myeloid leukemia: the availability of generic imatinib in the USA and the EU - Conti, Rena M.; Padula, William V.; Larson, Richard A. (Annals of hematology, 2015)
Imatinib is an oral tyrosine kinase inhibitor and considered to be the most successful targeted anti-cancer agent yet developed given its substantial efficacy in treating chronic myeloid leukemia (CML) and other malignant diseases. In the USA and the European Union (EU), Novartis’ composition of matter patent on imatinib will expire in 2016. The potential impact on health system spending levels for CML after generic imatinib becomes available is the subject of significant interest among stakeholders. The extent of the potential savings largely depends on whether and to what extent prices decline and use stays the same or even increases. These are also empirical questions since the likely spending implications following generic imatinib’s availability are predicated on multiple factors: physicians’ willingness to prescribe generic imatinib, molecule characteristics, and health system priorities. This article discusses each of these issues in turn. We then review their implications for the development of country-specific cost-effectiveness models to predict the implications for cost and quality of care from generic imatinib.